Developing A Supply Chain Of Apple Processed Product Traceability Information System Based On Smart Packaging And Digital Business Ecosystems - Kurniawan, Miftakhurrizal; Amalia, Faizatul; Setiyawan, Danang (Journal of Information Technology and Computer Science, 2021)
Apples are one of the fruits that much post-harvest processing can do. Apples can be processed into drinks or snacks. The need for information about nutritional content is needed by consumers. Therefore, a traceability information system is needed that can enable consumers to know the nutritional content involved. This research uses the Waterfall model information system development method and the Unified modeling language (UML). This method allows for the sequential development of information systems. The results of this research will be in the form of an information system that has been tested using the Requirement Traceability Matrix (RTM) and Response for a Class (RFC) method. The resulting Response for a Class (RFC) value is 5.17, meaning that this information system will be easy to adapt later